Intellectual property and confidentiality issues in senior design courses. - Goldberg, J.
Senior capstone design courses provide students the opportunity to develop their design skills and learn about the product development process. Student project teams, a number of which are industry-sponsored, often develop creative design solutions that result in the creation of intellectual property. When this occurs, who owns the intellectual property: the student, faculty advisors, industry sponsors, or academic institutions? The paper discusses how academic institutions, such as the Marquette University, deal with intellectual property and confidentiality issues in senior capstone design courses, in particular those that deal with biomedical engineering.
Keywords: Academic institutions; Biomedical engineering; Confidentiality; Creative design solutions; Design skills; Faculty advisors; Industry sponsors; Industry-sponsored student project teams; Intellectual property; Product development process; Senior capstone design courses